2012
DOI: 10.1007/s12015-011-9344-5
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Challenges of Ovarian Cancer Stem Cells: Novel Therapeutic Approaches

Abstract: Understanding the genetic and molecular mechanisms of ovarian cancer has been the focus of research efforts working toward the greater goal of improving cancer therapy for patients with residual disease after initial treatment with conventional surgery and neoadjuvant chemotherapy. The focus of this review will be centered on new therapeutic strategies based on Cancer Stem Cells studies of chemoresistant subpopulations, the prevention of metastasis, and individualized therapy in order to find the most successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 158 publications
0
35
0
Order By: Relevance
“…To determine if MORAB-003–induced autophagy links with cell death, we employed inhibitors of late-stage autophagy, including bafilomycin A1 (39) or hydroxychloroquine (HCQ) (40), to block the autophagic vacuolization and fusion. We found that both bafilomycin A1 and HCQ reversed the MORAB-003–induced reduction of cell viability in the SKOV3ip1 3-D spheroids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if MORAB-003–induced autophagy links with cell death, we employed inhibitors of late-stage autophagy, including bafilomycin A1 (39) or hydroxychloroquine (HCQ) (40), to block the autophagic vacuolization and fusion. We found that both bafilomycin A1 and HCQ reversed the MORAB-003–induced reduction of cell viability in the SKOV3ip1 3-D spheroids (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After the first description of stem cells in ovarian tumors nearly eight years ago [24], significant progress has been made towards identifying, characterizing and understanding CSCs and their role in ovarian cancer [32,47,48]. However, despite these advances, ovarian cancer patients are still faced with incurable chemoresistant disease that may be attributed to a population of CSC-like cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…In ovarian cancer, the CSC model has been postulated to drive tumor progression [2, 3, 38]. Numerous markers have been used to distinguish and characterize ovarian CSCs including CD133, CD44, CD117, epithelial cell adhesion molecule (EpCAM), CD24 and aldehyde dehydrogenase (ALDH) [2, 3942].…”
Section: Discussionmentioning
confidence: 99%